Welfare of fish - TSANTILAS (Η. ΤΣΑΝΤΗΛΑΣ), H.; ATHANASSOPOULOU (Φ. ΑΘΑΝΑΣΟΠΟΥΛΟΥ), E.; GALATOS (Α.Δ. ΓΑΛΑΤΟΣ), A. D.; BITCHAVA (Κ. ΜΠΙΤΧΑΒΑ), K. (Journal of the Hellenic Veterinary Medical Society, 2017)
Fish welfare and in general the welfare of animals is a term that declares a painless and not stressfull state of being. During the previous years this term has been questioned by the producers, however, nowadays, it is actually legally regulated in several countries. For fishes, few are the examples of such enforcement, such as in Norway and Germany where the killing of fish for human consumption bases on techniques compatible with their welfare. All the animals need a stable environment of being so that they can survive, develop and reproduce. The absence of such a stability is termed as stress. There are various causes of producing stress in fish. Firsdy, almost all management procedures that are practiced commercially result in stress (e.g. transport). Secondly, inadequate conditions of farming, such as the high stocking-density and an unbalanced food, place the welfare of fishes at risk. To the same result may also lead other factors, such as the unsuitable quality of the rearing water, the techniques that are used for the prevention and treatment of illnesses, the techniques of killing and also transport.